The Sacred books and early literature of the East: with historical surveys of the chief writings of each nation... - Horne, Charles F. (Parke, Austin, and Lipscomb, 1917)
I. Babylonia and Assyria.--II. Egypt.--III. Ancient Hebrew: the earliest remains, the Talmud.--IV. Medieval Hebrew: the Midrash, the Kabbalah.--V. Ancient Arabia: the hanged poems, the Koran.--VI. Medieval Arabic, Moorish and Turkish.--VII. Ancient Persia.--VIII. Medieval Persia.--IX. India and Brahmanism.--X. India and Buddhism.--XI. Ancient China.--XII. Medieval China.--XIII. Japan.--XIV. The great rejected books of the Biblical Apocrypha.